2013
DOI: 10.1155/2013/574260
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Beta-Aminopropionitrile and Prednisolone on the Prevention of Fibrosis in Alkali Esophageal Burns: An Experimental Study

Abstract: Objective. The aim of this study was to investigate the efficacy of beta-aminopropionitrile (BAPN) and prednisolone on the prevention of esophageal damage and stricture formation after caustic esophageal burn. Method. Twenty-eight rats were divided into four equal groups. In groups 1, 2, and 3, caustic esophageal burns were generated by applying NaOH to the 1.5 cm segment of the abdominal esophagus. Group 4 was for the sham. Normal saline to group 1, BAPN to group 2, and prednisolone to group 3 were administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 28 publications
(27 reference statements)
0
16
0
Order By: Relevance
“…[9] To reduce inflammation and collagen synthesis and to prevent fibroplasia and stricture formation, many clinical and experimental studies have evaluated the medical efficiency of antioxidant and anti-inflammatory agents, such as sucralfate, palifermin, dimethyl sulfoxide, prednisolon, retinoic acid, zinc, trapidil, trimetazidine, and pentoxifylline. [9][10][11][12][13]20,21] Despite decreased stricture formations in these studies, the rate of stricture formation remained at 70%-100% in highgrade corrosive esophagitis. [9] Garlic oil, a diallyl trisulfide, is the main active constituent of garlic and is one of the oldest medicine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[9] To reduce inflammation and collagen synthesis and to prevent fibroplasia and stricture formation, many clinical and experimental studies have evaluated the medical efficiency of antioxidant and anti-inflammatory agents, such as sucralfate, palifermin, dimethyl sulfoxide, prednisolon, retinoic acid, zinc, trapidil, trimetazidine, and pentoxifylline. [9][10][11][12][13]20,21] Despite decreased stricture formations in these studies, the rate of stricture formation remained at 70%-100% in highgrade corrosive esophagitis. [9] Garlic oil, a diallyl trisulfide, is the main active constituent of garlic and is one of the oldest medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Howell et al, [29] found that the steroidal treatment of corrosive esophagitis decreased the frequency of stricture formation. Aciksari et al, [13] compared the treatment effects of beta-aminopropionitrile (BAPN) and prednisolone and found that BAPN was better able to decrease the development of stenosis and tissue damage than prednisolone. In another study, [21] dimethyl sulfoxide was observed to reduce acute phase symptoms and to decrease the severity of tissue damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that honey also suppresses free radical production [6]. There are many studies demonstrating that granulation is prevented, and stricture formation is decreased by steroidal components [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…[9] Although many agents, including retinoic acid, pentoxifylline, sucralfate, N-acetylcysteine, antibiotics, and steroids have been used in both clinical and experimental studies to prevent the development of strictures, only antibiotics and steroids have gained clinical application. [10][11][12][13] MB was first identified as an antimalarial agent by Ehrlich in 1981, and it has since been used in many different areas of clinical medicine including treatment of refractory distributive shock, renal stones, carbon monoxide poisoning, methemoglobinemia, and encephalopathy for years due to its low toxicity and wide availability. [14,15] Most recently, MB was described as an effective product for preventing postoperative adhesions as well.…”
Section: Introductionmentioning
confidence: 99%